Measurement of Independent Learning Readiness of Prospective Teacher Students - Firdaus, Laras; Dewi, Ika Nurani; Samsuri, Taufik; Primawati, Sri Nopita (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Indonesia continues to be committed to improving the quality of human resources. This is realized through the Ministry of Education and Culture, which promotes and implements a curriculum that supports learning freedom. The application of this curriculum requires not only theoretical support but also more practical technical support, which cannot be ignored. In this regard, the Mandalika University of Education, especially the biology education department, has held workshops related to technical guidance for implementing the freedom to learn curriculum. However, it is essential to understand that there needs to be more information regarding the readiness of prospective biology teacher students to implement this curriculum. Therefore, this research was conducted to describe the level of readiness of prospective biology teacher students for independent learning. In this research, 53 prospective teacher students were involved voluntarily as respondents, including 42 women and 11 men, consisting of 12 (semester 1), 15 (semester 3), 17 (semester 5), and 9 (semester 7). The instrument used to measure the level of readiness for independent learning was adapted from the self-rating scale of self-directed learning (SRSSDL) questionnaire. Next, data regarding readiness for independent learning was analyzed descriptively and quantitatively. Based on the results of the analysis, it was found that 16.98% were not very ready (low or unprepared), 73.58% were not ready (moderate), and 9.43% were ready (high). These results also show that prospective biology teacher students have the same level of readiness for independent learning or that there is no significant difference in readiness for independent learning based on semester differences. Apart from that, of the SRSSDL components, self-awareness and learning activities have the lowest averages (32.51 and 32.09). Thus, our respondents (in this case, prospective biology teacher students) are not ready for independent learning. Regarding what will be done next, can be seen in the conclusions and recommendations section.